RECENT APPROACHES IN THE TREATMENT OF HODGKIN'S LYMPHOMA - Raida, Ludek (Biomedical papers, 1999)
factorsAn aim has been to find the optimal therapeutic approach for each patient suffering from Hodgkin s lymphoma.The disease with 80% curability rate presents the great success of clinical oncology. There is no doubt that thedevelopment and improvement of therapeutic approaches described in this article has contributed to the excellentresults achieved in the last twenty years. But a lot of problems still remain to be solved by haemato-oncologistsdespite such progress in the treatment. The most important tasks are: 1. to increase the curability of advancedstages, 2. to improve therapeutic results in refractory and relapsing patients, 3. to eliminate or decrease the latetoxicity particularly in the favourable early and intermediate stages.
Keywords: Hodgkin's disease / Radiotherapy / Chemotherapy / High-dose chemotherapy / Transplantation / Prognostic